1991
DOI: 10.1111/j.1365-2389.1991.tb00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heating on phosphate sorption and availability in some north‐east Nigerian soils

Abstract: Studies on phosphate sorption and availability in some north-east Nigerian soils showed that phosphate adsorption and inorganic-P concentrations increased considerably after the soil was heated either in a furnace or during the field-burning of straw. The increase in phosphate adsorption after heating was thought to be caused by an increase in free Fe and A1 oxides, whereas the high contents of exchangeable Ca and possibly carbonates and hydroxyl ions in the ash were probably responsible for the increase in ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Kuo (1988) reported a significant correlation between X m and the recovery of added P over a wide range of soils. This is not surprising as P deficient soils with a large sorption capacity can retain large quantities of P. Similar to the results of this study, Kwari and Batey (1991) observed an apparent enhancement of the effect of fire on maximum sorption capacity in a field burn with ash addition versus static oven heating. They suggested that the additional increase in sorption capacity with ash addition was due to the replacement of hydroxyl ions by the phosphate added in the ash.…”
Section: Maximum Soil P Sorption Capacitysupporting
confidence: 79%
See 1 more Smart Citation
“…Kuo (1988) reported a significant correlation between X m and the recovery of added P over a wide range of soils. This is not surprising as P deficient soils with a large sorption capacity can retain large quantities of P. Similar to the results of this study, Kwari and Batey (1991) observed an apparent enhancement of the effect of fire on maximum sorption capacity in a field burn with ash addition versus static oven heating. They suggested that the additional increase in sorption capacity with ash addition was due to the replacement of hydroxyl ions by the phosphate added in the ash.…”
Section: Maximum Soil P Sorption Capacitysupporting
confidence: 79%
“…These changes in soil mineralogy may be related to changes in P dynamics observed by Romanya et al (1994), Kwari and Batey (1991) and Serrasolsas and Khanna (1995). However, it is not well understood how heat-induced changes in texture and mineralogical composition affect the total surface area of mineral soil particles (as an indicator of P sorption capacity), the maximum amount of P that can be held by the soil (P sorption capacity, X m ) and the strength with which this P is retained to the soil particles (affinity constant, K).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have reported an increase in available soil P after heating (Kang & Sajapongse 1980;Kitur& Frye 1983;Kwari & Batey 1991) or in soils collected after a forest fire (Dymess et al 1989;Marion et al 199 1;Romanya et al 1994). Different mechanisms have been suggested to explain Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Kutiel & Shaviv (1989), in laboratory incubations, found an increase in P availability after soil heating, but after a few weeks available P decreased to the original values. Different reasons have been assigned for the decrease in available P in the longer-term after fire, which include changes in the mechanisms of phosphorus adsorption and desorption (Silva et al 1987;Kwari & Batey 1991;Romanya et al 1994), changes in the microbial population (Vazquez et al 1993), and changes in the microbial immobilisation and mineralisation of P (Dunn et al 1985;Polglase et al 1992).…”
Section: Introductionmentioning
confidence: 98%
“…A number of studies have found an increase in extractable inorganic P on low-temperature heating or drying of soils (Kwari & Batey, 1991;Grava et al, 1961;Serrasolsas & Khanna, 1995). The increase, according to Serrasolsas & Khanna (1995), could probably be due to solubilisation of a readily extractable fraction of the total P. In those studies, however, no mention is given on the source or mode of occurrence of the P in the heated or dried soils.…”
Section: R E S U L T S a N D Discussion Extractable Pmentioning
confidence: 99%